2022
DOI: 10.3390/v14102307
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Characterization of HIV-1 Sub-Subtype A1 in Karachi, Pakistan

Abstract: (1) Background: HIV-1 sub-subtype A1 is common in parts of Africa, Russia, former Soviet Union countries, and Eastern Europe. In Pakistan, sub-subtype A1 is the predominant HIV-1 subtype. Preliminary evidence suggests that distinct strains of HIV-1 sub-subtype A1 are circulating in Pakistan; however, an in-depth molecular phylogenetic characterization of HIV-1 sub-subtype A1 strains in Pakistan have not been presented. We performed a detailed characterization of the HIV-1 sub-subtype A1 epidemic in Pakistan us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Meanwhile, HIV-1 prevalence among men who have sex with men (MSM) has also increased (11%), making them another key HIV population group in Karachi ( 15 ). Previous studies have identified sub-subtype A1, CRF02_AG, CRF35_A1D, C, D, and G clades circulating among key HIV populations in Karachi ( 7 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, HIV-1 prevalence among men who have sex with men (MSM) has also increased (11%), making them another key HIV population group in Karachi ( 15 ). Previous studies have identified sub-subtype A1, CRF02_AG, CRF35_A1D, C, D, and G clades circulating among key HIV populations in Karachi ( 7 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pakistan has reported a 78.5% increase in new HIV infections in the last decade ( https://www.aidsdatahub.org ). Currently, 210,000 people are registered in different HIV treatment centers across the country ( 7 ). In Pakistan, the HIV-1 genetic diversity is becoming increasingly complex, with sub-subtype A1 and CRF02_AG being the most predominant clades responsible for approximately 68.1% and 16.5% of HIV-1 infections ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, HIV exists as a concentrated epidemic in key population groups such as people who inject drugs, transgender sex workers, male sex workers, men who have sex with men, and female sex workers, where the prevalence is approximately 38.4%, 7.5%, 5.6%, 5.4%, and 2.2%, respectively [2,3]. Furthermore, the number of new cases has increased rapidly in the past 10 years, and several new outbreaks have occurred in Pakistan in recent years, including the 2019 HIV outbreak in Larkana, where more than 1,000 children were found infected with HIV [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%